The Role Of Pediatric Nurses In Caring For Children With Covid 19 In Indonesia - Hastuti, Dwi; Fauziah Rudhiati; Chatarina Suryaningsih (STIKep PPNI Jawa Barat, 2021)
Aims : Children are the most vulnerable age for COVID-19 due to an immature immune system and low ability to apply prevention protocol. A total of 7,950 children from 34,211 confirmed positive children in Indonesia must receive treatment. Special treatment for COVID-19 children apart from being in isolation rooms, not allowing family members to accompany them, and limiting interactions between patients and nurses (Members of the Divisions of Pediatric Infectious Disease, 2020). This study aims to determine the role of pediatric nurses in providing care for children with COVID-19 at the hospital. Design : The design of this research is exploratory qualitative. The method of collecting data with focus group discussions is using an online interaction application. Methods : Explorative qualitative research design with Focus Group Discussion (FGD) method. The selection of participants by purposive sampling. The participants is 10 nurses with the criteria of working in the Covid isolation children's room, working more than 1 year in the hospital. Data retrieval is done online via the zoom application using mobile devices, field notes, stationery and laptops. Data analysis with Colaizzi analysis method. Results : The results of the study obtained themes is the role of nurses, efforts made by nurses, obstacles experienced by nurses, nurses expectations, nurses joys and sorrows, patient and family responses, support for nurses. Conclusions : Recommendation for hospitals to pay more attention to the welfare and work safety of nurses and the community are expected to comply with health protocols correctly.